Go Digital: Empowering Village MSMEs Through Social Media and Qris - Solihat, Asri; Sugiarto, Hendro; Fadillah, Fahmi (Indonesian Journal of Community Empowerment (IJCE), 2025)
The use of social media not only provides opportunities for more efficient marketing but also helps build strong brand awareness among consumers. However, there remains a gap in digital literacy and skills among MSME entrepreneurs in rural areas, necessitating a comprehensive training program to bridge this gap. This community service program is designed through a participatory, educational, and applied approach, so that village MSMEs not only gain knowledge but also practical skills that can be immediately applied. This program is designed to address the challenges faced by village MSMEs in the digital era, where social media-based marketing and digital payment systems like QRIS have become fundamental requirements for business continuity. The results of this program demonstrate that the digitalization of village MSMEs is not merely an option but an urgent need. The use of social media has proven to expand market reach, while QRIS provides a practical and secure payment solution.